"Há sempre confiança de se estar ligado a alguém": dimensões utópicas das expressões da religiosidade bantú no Brasil - Malandrino, Brígida Carla (2010)
The subject under study in this work are the expressions of bantu religiousness in Brazil, emphasizing the utopian form, that is, the desired and transitory form according to the view of Religion Sciences. We worked with the hypothesis that the religious expressions of the groups of bantu tradition in Brazil, throughout history, can be understood as forms of continuity, but we also understand that there is no such thing as a uniform whole, but that some aspects are recovered, others are discarded and yet others are transformed, as a way of achieving a symbolic reorganization. The formation of new religious expressions, such as umbanda, represented this attempt by people. To start, in a preliminary form, we touched the question of the bantu tradition. Then we talked about the Diaspora process and the transformation of the free African into a slave in Brazil. After that, we considered the period of slavery in Brazil, focusing on the relationship of the Catholic Church to slavery, talking about Afro-Brazilian practices of bantu tradition, during this period. Next we worked the periods pre and after abolition, when a new identity change happened, that is, from slavery to freedom. From this point on, we talked about umbanda; first as a bantu utopia, then we go on as almost a follow up of the Fifth Chapter, talking about the bantu aspects in umbanda nowadays. It is possible to state that, according to this work, we have achieved the following results: we have identified the influence of the bantu tradition in umbanda; we got the understanding of how people belonging to a specific tradition, in this case, the bantu tradition, have managed to give new meanings to their religious practices throughout time; and we have offered contribution for the understanding of hybrid religious practices, doing a first approximation in the sense of offering a reading key or a method to understand a diasporic tradition, in our case, from a bantu tradition standpoint. Specifically we have written about the creation of a method for the understanding of survivals translated from diasporic traditions